Pengaruh Profitabilitas, Leverage, Firm Size, dan Firm Age Terhadap Tax Aggressiveness Perusahaan Healthcare Yang Terdaftar BEI Tahun 2020-2024 - Apandi, Dwi Ayu; Santoso, Budi (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This study aims to analyze the impact, both separately and simultaneously of probitality, leverage, firm size, and firm age on tax aggressiveness in healthcare companies listed on the Indonesia Stock Exchange (IDX). This study is quantitative, with data taken from secondary sources orginating from the official website www.idx.co.id or the company’s own website. The sample selection technique used was purposive sampling, resulting in 12 companies over a five-year period. To analyze the data, a panel data regression method was applied and processed using Eviews version 13. The findings of this study indicate that profitability and firm age have a separate influence. However, there is no partial effect shown by leverage and firm size. In addition, overall profitability, leverage firm size, and firm age influence tax agggressiveness